EU energy taxation framework revision in the context of the green deal: Towards a green, efficient, socially just, and inclusive economy transition - Antón Antón, Álvaro (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
The EU aims to reduce emissions by at least 55% by 2030. To achieve this, the European Commission launched proposals to introduce price signals through the modification or extension of the Emission Trading Scheme and the Energy Tax Directive. These instruments could have a negative impact on households and companies' competitiveness. This research focuses on the one hand, on the role of energy taxation in the achievement of climate objectives and budget stability. And, on the other, in analysing the role of taxation to develop compensatory measures so that the transition is efficient, socially fair and inclusive.